The influence of mindfulness-based interventions on the academic performance of students measured by their GPA. A systematic review and meta-analysis - Ostermann, Thomas; Pawelkiwitz, Martin; Cramer, Holger (Frontiers in Behavioral Neuroscience, 2022)
Objective: Mindfulness-based interventions are increasingly used in health, economic and educational systems. There are numerous studies demonstrating the effectiveness of mindfulness-based interventions in the educational sectors (primary, secondary and tertiary). This systematic review and meta analysis assessed the current state of research on the effectiveness of mindfulness-based interventions on the academic performance of students as measured by their grade point average (GPA). Methods: Literature search was conducted in Psychology and Behavioral Sciences Collection, PsycARTICLES, PubMed and Google Scholar through March 2022. The inclusion criteria were: (1) the use of GPA as a measure of students’ academic performance, (2) a sample that was subjected to a mindfulness-based intervention without medical indication, (3) the student status of the subjects. Meta-analysis was conducted using a random effects model with the generic inverse variance method. Results: The search included a total of 759 studies, of which 6 randomized controlled trials met the inclusion criteria. In these trials significant group differences for GPA were found with effect sizes ranging from d=0.16-1.62 yielding a significant overall effect of d=0.42 (95% CI: 0.15 – 0.69] and a low magnitude of heterogeneity of I2=37%. Discussion: In conclusion, the first results of this emerging research field seems promising. However, the exact mechanisms of action are still unclear.